Ecosystem evaluation of post sand mining land in Cimalaka, Sumedang - A R F Sholihah; A Sjarmidi (Journal of Degraded and Mining Lands Management, 2014)
This research was conducted to evaluate ecosystem function of post-sand mining land in northern side of Layapan, Cimalaka, Sumedang, West Java (S 6o 47’ 33.68” and E 107o 58’18.73”, 744 m above sea level). Microclimate and soil characteristics measurements were carried out to describe the physical and chemical characteristics of the land. Vegetation analysis was conducted with plotting method. Ecosystem Function Analysis, including Landscape Function Analysis (LFA) has been used to analyze the function of landscape. The results showed that average light intensity, air temperature and humidity were 15.2x103 ± 7.3x103 lux, 29.1±1.02oC and 69.7±7.5%. High light intensity made the air temperature rouse higher than normal, which is between 17.1oC to 22oC. As for the soil, soil organic content was 4-11%, porosity 4.65-24.43%, macronutrient content was low and C/N ratio was high. The results showed that LFA value for land stability was 33.24%, water infiltration 37.2%, nutrient cycle rate 15.28%. Those numbers showed that land condition was poor. From the LFA data, it was also known that vegetations had the highest contribution for all LFA parameters. From vegetation analysis, herbs species were 67 while bushes only 9, which at least 40 species were invasive alien species. Species with highest Important Value (IV) from herb was Cajanus scarabaeoides and from bush was Mimosa pigra. Both of them are members of Fabaceae. It was concluded that the soil of this post sand mining land was highly nutrient poor; critical and couldn’t perform the regulation, habitat and biomass production function of ecosystem.